Monitoring system for small sized photovoltaic power plants - Correia, Daniel (2017)
This paper presents a monitoring system devoted to small sized photovoltaic (PV) power plants. The system is characterized by: a high level of integration; a low cost, when compared to the cost of the PV system to be monitored; and an easy installation in the majority of the PV plants with installed power of some kW. The system is able to collect, store, process and display electrical and meteorological parameters that are crucial when monitoring PV facilities. The identification of failures in the PV system and the elaboration of performance analysis of such facilities are other important characteristics of the developed system. The access to the information about the monitored facilities is achieved by using a web application, which was developed with a focus on the mobile devices. In addition, there is the possibility of an integration between the developed monitoring system and the central supervision system of Martifer Solar (a company focused on the development, operation and maintenance of PV systems).